1999
DOI: 10.1073/pnas.96.21.11982
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin gene transfer corrects diastolic dysfunction in diseased cardiac myocytes

Abstract: Heart failure frequently involves diastolic dysfunction that is characterized by a prolonged relaxation. This prolonged relaxation is typically the result of a decreased rate of intracellular Ca 2؉ sequestration. No effective treatment for this decreased Ca 2؉ sequestration rate currently exists. As an approach to possibly correct diastolic dysfunction, we hypothesized that expression of the Ca 2؉ binding protein parvalbumin in cardiac myocytes would lead to increased rates of Ca 2؉ sequestration and mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
60
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 20 publications
7
60
0
Order By: Relevance
“…In parallel with the improvement in calcium decay rate, we also found that the rate of myocyte relengthening is dramatically increased in senescent myocytes expressing parvalbumin and in fact slightly exceeds the relaxation rate of adult control myocytes. These results are consistent with the findings of Wahr et al, 9 who demonstrated that relaxation parameters in both hypothyroid and healthy myocytes were significantly ameliorated with parvalbumin, with no effect on the rate of cell shortening or the amplitude of peak contraction.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In parallel with the improvement in calcium decay rate, we also found that the rate of myocyte relengthening is dramatically increased in senescent myocytes expressing parvalbumin and in fact slightly exceeds the relaxation rate of adult control myocytes. These results are consistent with the findings of Wahr et al, 9 who demonstrated that relaxation parameters in both hypothyroid and healthy myocytes were significantly ameliorated with parvalbumin, with no effect on the rate of cell shortening or the amplitude of peak contraction.…”
Section: Discussionsupporting
confidence: 82%
“…3 Adenoviral gene transfer of parvalbumin into cardiac myocytes has shown that both the rate of calcium transient decay and the rate of myocyte relaxation are increased by the introduction of parvalbumin, with no decrease in contraction amplitude. 9 This effect is observed both in healthy adult myocytes and in a disease model of diastolic dysfunction (hypothyroidism) in which expression of parvalbumin fully corrected relaxation parameters (t 1/2R and ϪdL/dT) in myocytes from diseased animals back to normal (euthyroid) levels. Further confirmation of the ability of parvalbumin to restore diastolic parameters to normal was obtained in an in vivo setting, in which injection of parvalbumin into the LV free wall both accelerated myocardial relaxation under physiological conditions and improved myocardial twitch relaxation rates and ϪdP/dt in hypothyroid hearts to normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a calcium affinity that is intermediate between troponin and SERCA, allowing it to act as a Ca 2ϩ sink to temporarily bind Ca 2ϩ before SR uptake. PV gene transfer is one approach that has recently been used successfully to target prolonged relaxation in a rodent model of diastolic dysfunction in short term (15). Adenoviral transduction of PV into the LV free wall has been shown to accelerate LV isovolumic relaxation times significantly in normal animals and also to restore normal relaxation performance in hypothyroidism-induced diastolic dysfunction (15).…”
Section: Discussionmentioning
confidence: 99%
“…PV gene transfer is one approach that has recently been used successfully to target prolonged relaxation in a rodent model of diastolic dysfunction in short term (15). Adenoviral transduction of PV into the LV free wall has been shown to accelerate LV isovolumic relaxation times significantly in normal animals and also to restore normal relaxation performance in hypothyroidism-induced diastolic dysfunction (15). However, overexpression of PV in our model did not mitigate the effects of I͞R on contractile dysfunction in the anterior wall, as evidenced by the echocardiographic data, and did not decrease the incidence of arrhythmias.…”
Section: Discussionmentioning
confidence: 99%